Tawhidic Moral Ecology: A Framework for Character Education in Islamic Homeschooling - Komarudin, Yahya (Advances in Humanities and Contemporary Studies, 2026)
This study explores the process of internalizing the value of tawhid (the oneness of God) within Islamic homeschooling education in Bandar Lampung, Indonesia, through the theoretical framework of Thomas Lickona’s moral development model, which encompasses three dimensions: moral knowing, moral feeling, and moral action. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation. The findings reveal that tawhidic values are systematically implemented across all moral dimensions. In the moral knowing phase, children are guided to understand the concept of divine unity through muzakarah (dialogic learning), storytelling, nature contemplation (tadabbur al-nature), and problem-based learning. In the moral feeling phase, these values are internalized through modeling, habituation, and reflective dialogue, cultivating both emotional and spiritual awareness. In the moral action phase, tawhid is manifested in practical behavior through exemplary conduct, worship habituation, value dialogue (hiwar al-qiyam), assigned responsibilities, and community-based social projects. This study affirms that tawhid serves as the core of moral character formation within Islamic homeschooling—an integrative and contextually grounded framework for nurturing faith-based moral development in children.